PENGARUH PENERAPAN ISO/IEC 17025:2005 TERHADAP KOMPETENSI LABORATORIUM PENGUJIAN BALAI BAHAN PERKERASAN JALAN DI BANDUNG - M. Tranggono (Direktorat Bina Teknik Jalan dan Jembatan, 2006)
The management of laboratory testing is highly important in achievement of certain level of qualitu standard that will be effected to the accuracy of testing result or their technical competence. Main focus of this study to evaluate the influence of application ISO/IEC 17025 to technical competence of